Pengaruh “Cyberbullying” Melalui Media Sosial Terhadap Tingkat Kecemasan Remaja - Isak Iskandar; Ummu Salamah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the effect of Cyberbullying through social media on anxiety levels in adolescents. The background of this study is based on the increasing use of social media among adolescents followed by the risk of online bullying (Cyberbullying), which can affect mental health, especially anxiety. This study uses a quantitative approach with a correlational survey method. The subjects of the study were adolescents aged 13–18 years who actively use social media. The sampling technique used purposive sampling with a total of 20 respondents. The instruments used were Cyberbullying scale questionnaires and anxiety scales. The results showed that there was a significant influence between Cyberbullying and adolescent anxiety levels. The higher the level of exposure to Cyberbullying, the higher the level of anxiety felt by adolescents. These results indicate that Cyberbullying is a factor that needs serious attention in efforts to prevent mental health disorders among adolescents.